COMPARATIVE ANALYSIS OF THE EFFICIENCY OF APPLICATION SOFTWARE PRODUCTS FOR PLACEMENT OF VACUUM RECLOSERS IN THE DISTRIBUTION CHANNEL - Gai, A.; Zavodovsky, O.; Petrov, P. (Енергетика і автоматика, 2016)
The comparative analysis of efficiency of application software products for placement of vacuum reclosers in the distribution network. The examples and the task of further research.